Study of impulse buying on Instagram users in Indonesia - Sri Rahayu Tri Astuti; Imroatul Khasanah; Y Yoestini (Diponegoro International Journal of Business, 2020)
Our paper is aimed to find out the effect of online advertisement content, electronic word of mouth (e-WOM) and hedonic shopping motives on impulse buying of Indonesian users in Indonesia. Multiple linier regression analysis is used to examine the magnitude of independent variables effect which are online advertisement content, e-WOM  and hedonic shopping motives on impulse buying on instagram user in Indonesia. The analysis on 75 respondents showed that all independent variables have positive and significant effect on dependent variable. The independent variabel which has the biggest effect on impulse buying in order are online advertisement content, e-WOM and hedonic shopping motives. The main reason affecting the decision from impulse buying is good online advertisement content which is marked by informative, easily understood, easily accessed contents and its attractive visualisation. The practical implications of this study are of most interest for advertisers, marketers, online retailer and designers of shopping website.